STUDY OF POLYSACCHARIDE COMPLEX OF SORBARIA SORBIFOLIA LEAVES - M. E. Guschina; S. L. Adzhiakhmetova; E. T. Oganesyan (Фармация и фармакология (Пятигорск))
We have isolated polysaccharides and identified monosaccharides after hydrolysis during the work. Gravimetric analysis identifies the prevalence of pectin substances (PS) and hemicelluloses A (HC A).